Digitalization of Performance and Compensation Excellence: Analyzing Employee Performance in Government Training Institutions thru a Mediation Model - Liza Nofia; Sri Lestari Prasilowati (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2026)
Digitalization in the public sector has changed the paradigm of performance management, yet the role of compensation as a driver of productivity remains a crucial debate. This study aims to analyze the influence of E-Performance, Transformational Leadership, and Job Satisfaction on Employee Performance at the Health Training Centre (Bapelkes) Cikarang, with Compensation as an intervening variable. Using a quantitative approach with the Structural Equation Modelling (SEM-PLS) method, data were collected from the entire employee population thru structured questionnaires. The results of the data analysis show that E-Performance and Compensation have a direct, positive, and significant impact on employee performance. Conversely, Transformational Leadership and Job Satisfaction were found to have no direct impact on performance. The most crucial finding indicates that Compensation acts as a full mediator in the relationship between Job Satisfaction and Employee Performance. This implies that employee satisfaction can only be converted into actual productivity if supported by a fair and transparent reward system. The IPMA analysis emphasizes that the integration of digital reporting and incentive schemes is a strategic priority to maintain the stability of institutional productivity in the long term